Regional water resources carrying capacity in China based on analytic hierarchy process and system dynamics model: a case study of Golmud City - Sun, Yongshuai; Wang, Yiling; Zhang, Wei; Ye, Shuigen (Frontiers in Environmental Science, 2024)
Water resource carrying capacity is a critical measure of the ability of water resources within a region to support social, ecological, and economic scales. This study establishes an evaluation index system for the water resource carrying capacity of Golmud City and calculates the weights of the indices using the Analytic Hierarchy Process (AHP). Based on an analysis of the current status of Golmud 's socioeconomic development, agriculture, and water resource utilization, a simulation model based on system dynamics is constructed. By setting 162 different scenario plans and normalizing the simulation results, the development trend of Golmud City's water resource carrying capacity is studied, and an evaluation is made for the sustainable development of water resources in Golmud City. Using data from 2001 to 2018 as the basic data, a carrying capacity analysis of water resources for the future from 2019 to 2030 is conducted. The study reveals that continuing the current development pattern will lead to unsustainable water resource carrying capacity. Among the scenarios aimed at coordinated development in all aspects, the best water resource carrying index is achieved, reaching 0.698 by 2030. By analyzing the development trend of the water resource carrying capacity index, existing problems in the utilization of water resources in Golmud City are identified, and feasible strategies for the sustainable use of water resources in Golmud City are proposed.